Knowledge Economy Dimensions - Constantin BRĂTIANU; Violeta Mihaela DINCĂ (Revista de Management Comparat International)
The purpose of this paper is to present an analysis of the emergent knowledge economy and its dimensions. The knowledge economy is based primarily on the development of intangibles, and knowledge processing. The knowledge revolution is changing the way we think and work, and the knowledge worker reflects the nature of the new economic driving forces. The knowledge economy opens new directions, and offers unprecedented opportunities to produce and sell on a mass scale, reduce costs, and customize to the needs of consumers, all at the same time. The dimensions of this new economy are the following: economic and institutional regime, education and skills, information and communication infrastructure, and the innovation system. Based on these dimensions, the World Bank Institute developed two important indices: the Knowledge Index (KI), and the Knowledge Economy Index (KEI).